Game-Based Archery Learning in Physical Education: A Qualitative Exploration of Elementary School Students' Attention Experiences - Sudisto, Sudisto; Gunawan, Agus (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study aims to qualitatively explore students' attention experiences during game-based archery learning in elementary school physical education. Materials and methods. This study employed a qualitative approach with a case study design. Participants were 40 fifth and sixth grade elementary school students (20 students from MIMHA Elementary School and 20 students from Istiqomah Elementary School) aged 10-12 years. Data were collected through video observation (3 videos) and analysis of 3 educational images. Data analysis used thematic analysis (Braun & Clarke, 2022) with stages of open coding, axial coding, and selective coding. Results. This study identified 33 open codes (OC1-OC33) grouped into 7 categories and produced 3 main themes. The first theme is Game-Based Learning Implementation which reflects the S1-S6 game structure. The second theme is Attention & Executive Function which shows an increase in students' selective and sustained attention as indicated by pause behavior before release (1-2 seconds). The third theme is Social & Discipline Context which reflects social interaction and the formation of discipline without coercion Conclusions. This qualitative study suggests that game-based archery learning appears to support attention among elementary school students based on participant reports and observation. A notable finding is students' subjective experience of sustained attention, which differs methodologically from Mo et al. (2024) meta-analysis that found non-significant quantitative effects. The S1-S6 game structure is proposed as a tentative framework for game design in precision sports contexts. Further quantitative research is needed to test these qualitative insights.